Impact of Oral Diseases on Systemic Health in the Elderly: - George W. Taylor, DMD, DrPH; Walter J. Loesche, DMD, PhD; Margaret S. Terpenning, MD (Blackwell Synergy, 2000)
Evidence is increasing that oral health has important impacts on systemic health. This paper presents data from the third National Health and Nutrition Examination Survey (NHANES 111) describing the prevalence of dental caries and periodontal diseases in the older adult population. It then evaluates published reports and presents data from clinical and epidemiologic studies on relationships among oral health status, chronic oral infections (of which caries and periodontitis predominate), and certain systemic diseases, specifically focusing on type 2 diabetes and aspiration pneumonia.